Innovation Capability In The New Normal Era - Albert, Albert; Rini, Endang Sulistya; Bhastary, Manda Dwipayani; Djohan, Deva; Kosasih, Hengky (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
The purpose of this study is to build a model of innovation capability, co-creation, and value based selling on the marketing performance of dodol entrepreneurs in North Sumatra. This study uses an explanatory research type with a quantitative approach. Questionnaires were given to the Dodol UKM craftsmen in North Sumatra as many as 60 respondents with a sample technique using a purposive sample based on predetermined criteria. Analysis of the data using descriptive statistics and hypothesis testing using path analysis smartpls. Based on the test, it is explained that the overall hypothesis in the study has a positive and significant effect. First, the Co Creation variable has a positive and significant effect on the innovation capability variable and the marketing performance variable. Furthermore, the Value-based selling variable also affects the innovation capability variable and the marketing performance variable. The innovation capability variable also has a positive and significant effect on marketing performance.